Die ersten amurritisch-akkadischen Bilinguen: eine Nachlese nebst einem Vergleich mit dem "Rosen Vocabulary" - Krebernik, Manfred (Die Welt des Orients, 2025)
The article offers some additional considerations and suggestions concerning the interpretation of the Amorite-Akkadian bilinguals published by A. George and M. Krebernik in RA 116 (2022) 133-166, including a comparison between the bilinguals and the "Rosen Vocabulary" published by C. J. Crisostomo in ZA 106 (2016) 22-32.